2016
DOI: 10.18538/lthe.v13.n1.232
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in students’ ratings of university teachers in the Iranian education system

Abstract: University students' ratings of teaching and teachers' performance are used in many parts of the world for the evaluation of faculty members at colleges and universities. Even though these ratings receive mixed reviews, there is little conclusive evidence on the role of the intervening variable of teacher and student gender in these ratings. Possible influences resulting from gender-related differences in different sociocultural contexts, especially where gender combination in student and faculty population is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…So, by considering the qualities preferred by both male and female learners, teachers can also modify their teaching styles. But while considering students" ratings for designing lesson plans teacher should be very cautious as there are different dynamic variations in their perceptions of effective teaching [20].…”
Section: ) Summary Of the Discussionmentioning
confidence: 99%
“…So, by considering the qualities preferred by both male and female learners, teachers can also modify their teaching styles. But while considering students" ratings for designing lesson plans teacher should be very cautious as there are different dynamic variations in their perceptions of effective teaching [20].…”
Section: ) Summary Of the Discussionmentioning
confidence: 99%
“…In Iran, researchers designed a questionnaire to assess potential gender biases in faculty ratings by male and female students (Zare-ee et al, 2016). The study, based on 800 randomly sampled student evaluations, indicated that male students rated female faculty lower than male faculty (p 5 0.001) (Zare-ee et al, 2016). The researchers noted that the effects of this variable may vary based on contextual factors and student expectations.…”
Section: Student Evaluations Of Faculty Competency International Rese...mentioning
confidence: 99%
“…Notably, a university study in France found that male students were more likely to give higher satisfaction scores to male teachers than female teachers. Similarly, in Iran, male students tended to rate female faculty lower than their male counterparts (Zare-ee et al ., 2016). Also, The Rate my professor (2014) Website contains potential gender bias in student ratings, emphasizing the need for a more in-depth exploration of student descriptions of faculty competency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations